Translanguaging Practices Among Students: A Case Study at a Public Vocational School - Fernanda, Aviq Yusuf; Triyoga, Arilia (Universitas Ahmad Dahlan, 2025)
Multilingualism is defined as having the ability to use and understand many languages, including situations where individuals or communities show proficiency in several languages. This study investigates the types, influencing factors, and advantages of translanguaging practices among vocational school students. The method employed in this research is a qualitative research method, case study design, conducted at a public vocational school in Yogyakarta. The research subject in this study consists of four students. The instruments used to gather data include an observation checklist, documentation, and interview guidelines. The researcher collected the data through observation and voice recording for the interview. It uses data reduction, data display, and conclusion drawing for data analysis. The findings of this research indicate that vocational school students engage in three forms of translanguaging in the classroom: intra-sentential, inter-sentential, and tag translanguaging. Moreover, three main factors are identified as encouraging students to apply translanguaging: first, the spontaneous act in which language is used; second, the class is enjoyable and engaging for the experience when using translanguaging; and third, the students' ability to adapt to a learning environment that accommodates such language practices. This research emphasizes the significance of translanguaging within multilingual educational settings, particularly in Indonesian vocational schools. It demonstrates that permitting students to alternate between their first language (L1), second language (L2), and English (L3) enhances both their comprehension of vocational material and English language skills.